Prioritizing based on crowd preferences to requirements elicited from crowd's sentiments - Abdul Aziz, Nurul Afiqah; Hassan, Sa’adah; Admodisastro, Novia Indriaty (International Journal of Innovative Technology and Exploring Engineering, 2019)
The current trend in software engineering is using crowd as source of ideas for developing software product. Crowd is described as a large and heterogeneous group of stakeholders. Crowd is also used as a source of requirements, for example, the requirements can be elicited from their reviews, reports, or feedback. However, the challenge is to prioritize the requirements knowing that the data is also large and heterogeneous. Requirements prioritization is an approach to identify requirements that need to be selected and implemented first in software development. This paper presents an approach to prioritize requirements elicited from crowd and the prioritization is based on the crowd preferences in order to ensure the customer satisfaction. A prototype tool is developed as a proof-of-concept and evaluation purposes. It is expected that the proposed approach able to helps developer to prioritized requirements based on customers’ preferences as it would consider their satisfaction of the software product.